Artificial intelligence is important! A mini systematic literature review of bioethics in science learning - Atok Miftachul Hudha; H. Husamah; Intan Kristina Permatasari; Mella Anggi Puspitasari; S. Silvia (Research and Development in Education (RaDEn), 2024)
The focus and concern of researchers on the theme of bioethics and its relationship with science learning is highly expected, as evidenced by publications in reputable journals. The purpose of this systematic literature review (SLR) was to review and compare investigations of researches on article published by scopus indexed journals. We used the phrase "bioethics+learning+science" in the search menu of the scopus database, and found 138 articles. Furthermore, 15 articles met the criteria to be analyzed. The inclusion and exclusion model used is PRISMA. The publication of "bioethics" in the scopus database is likely to increase in 2012. Although in 2013-2022 there were fluctuations. This theme can be approached through qualitative or quantitative and even mix-method. Almost all types of populations/samples have been used as subjects, showing that this theme is broad in dimension and involves all parties. Leonora Kaldaras is the most dominant researcher in reference. Bioethics specs are related to artificial intelligence. The keyword artificial intelligence is related to student, teaching, engineering education, computer science education, education computing, and education. Interesting things on the theme of artificial intelligence related to learning systems and computer aided instruction. The theme of "bioethics" is the focus of researchers from all continents and is generally written in groups. There are four institutions in the world that fund research and publications on bioethics, while the others are not mentioned. Most publications have fulfilled one of the ethics in publication, which is to clearly mention the name of the institution / institution that funds their research and publication. We formulate and discuss all aspects of the trend. The alignment of researchers continues to increase regarding "bioethics", which can be seen based on distribution year, research types / methods, instruments, aspects of study, author, keywords, author's internationality, and collaboration. This information or findings gives us new insights to think clearly about research and the relationship between bioethics, science learning and artificial intelligence.